Assembling hierarchical metal–oxygen building units with a semirigid tetracarboxylate ligand into a three-dimensional framework for nitrobenzene sensing. Issue 20 (5th May 2017) - Song, Xue-Zhi; Gao, Li-Guo; Wang, Yu-Xiang; Chen, Xiao-Lei; Qiao, Liang; Tan, Zhenquan
Abstract : A three-dimensional framework collecting hierarchical metal–oxygen multicluster, macrocyclic, and infinite chain-like building units was fabricated and investigated as efficient luminescent sensor towards nitrobenzene. Abstract : In this study, a dense three-dimensional framework (compound1 ) was elaborately fabricated by the assembly of hierarchical metal–oxygen multicluster structural units, macrocyclic structural units, and infinite chain-like building units with a semirigid tetracarboxylate ligand. The good photoluminescent property endows compound1 with the ability to selectively detect nitrobenzene.